The role of SATB2, CDX2, CK7 and CK20 in differentiating primary versus metastatic ovarian carcinoma - Sana Tahir; Lubna Avesi; Saba Hassan Shamim; Farheen Danish; Uzma Bukhari; Farah Muhammad Ali (Khyber Medical University Journal, 2024)
OBJECTIVE: To find out the association of primary ovarian carcinomas (POC) and metastatic gastrointestinal carcinoma (MGC) by utilizing a panel of antibodies including Cytokeratin (CK) 7, CK20, Caudal-type Homeobox Transcription Factor-2 (CDX2), and SATB2 with their clinicopathological parameters. METHODS: This prospective cross-sectional study was conducted from Mar, 2023 to Dec 2023 at Dow University of Health Sciences, Karachi, Pakistan. Biopsy tissue specimens from female patients over the 40 years, diagnosed with primary and metastatic ovarian carcinomas (MOC), were included. Immunohistochemistry, employing a three-tier scoring system, assessed CK7, CK20, CDX2, and SATB2 expressions. Statistical analysis was performed, utilized SPSS version 26.0 by employing Chi-Square test. RESULTS: Over a 9-month period, 100 biopsied tissue samples were collected from patients aged 42-71 years (mean age 53.24 ± 8.03 years). Among these, 79 were POC (51% serous carcinoma, 9% mucinous carcinoma, 18% endometrioid carcinoma, and 1% clear cell carcinoma), and 21 were MGC. CK7 showed diffuse staining predominantly in POC and was absent in MGC (p < 0.001). CK20 exhibited significant focal and diffuse staining in MGC and was largely absent in POC (p = 0.005). CDX2 was significantly absent in POC and showed diffuse and focal staining in MGC (p < 0.001). SATB2 was absent in POC and displayed focal or diffuse staining in MGC (p < 0.001). CONCLUSION: The inclusion of SATB2 in immunohistochemical panels, alongside CK7, CK20, and CDX2, improves the accuracy of diagnosing primary and metastatic ovarian carcinomas. This approach provides support in the distinction between ovarian and gastrointestinal tumors.